2020
DOI: 10.1002/adma.202002401
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Behavior of 2D Janus Excitonic Layers under Extreme Pressures

Abstract: Newly discovered 2D Janus transition metal dichalcogenides layers have gained much attention from theory perspective owing to their unique atomic structure and exotic materials properties, but little to no experimental data are available on these materials. Here, our experimental and theoretical studies establish the vibrational and optical behavior of 2D Janus S-W-Se and S-Mo-Se monolayers under high pressures for the first time. CVDgrown classical TMD monolayers were first transferred onto vdW mica substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 43 publications
4
43
1
Order By: Relevance
“…The observed Raman spectra also differ significantly from 2D alloy WSSe [25] and MoSSe [26,27] (see Figure S3, Supporting Information). Moreover, our calculated vibrational dispersion, together with the published predictions for WSSe and MoSSe [7,8,14,28] match reasonably well with our experimental datasets with a deviation of around 1.1-2.8%, as shown in Figures S4 and S5, Supporting Information, and Table 1. These observations again validate that the as-synthesized layers have Janus structure instead of random alloying.…”
Section: Janus Crystals Represent An Exciting Class Of 2d Materials Wsupporting
confidence: 84%
“…The observed Raman spectra also differ significantly from 2D alloy WSSe [25] and MoSSe [26,27] (see Figure S3, Supporting Information). Moreover, our calculated vibrational dispersion, together with the published predictions for WSSe and MoSSe [7,8,14,28] match reasonably well with our experimental datasets with a deviation of around 1.1-2.8%, as shown in Figures S4 and S5, Supporting Information, and Table 1. These observations again validate that the as-synthesized layers have Janus structure instead of random alloying.…”
Section: Janus Crystals Represent An Exciting Class Of 2d Materials Wsupporting
confidence: 84%
“…However, the underestimated band gaps will be compensated for by the absence of SOC in the calculations. The net effect is that, for example, the PBE band gaps of WSSe and MoSSe agree well with the experimental band gaps [98]. We use a Monkhorst-Pack [99] 15  15  1 k-point grid.…”
Section: Methodsmentioning
confidence: 94%
“…The PBE‐calculated optical band gaps of WSSe and MoSSe agreed well with the experimental band gaps. [ 54,55 ] A Monkhorst–Pack [ 56 ] 15 × 15 × 1 k ‐point grid was used. The in‐plane lattice constants and atomic coordinates of all systems were fully optimized using a quasi‐Newton algorithm with the force convergence criterion of 0.01 eV Å −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Their vibration modes are lack of monotonic response to pressure. [162] Furthermore, pressure-dependent phonon dynamics of black phosphorus are also discussed experimentally and theoretically (Figure 5c,d). [33] It is concluded that: 1) FWHM of first-order Raman modes attain a minimum at ≈1.1 GPa and this is associated with the anomalies of electron-phonon coupling at electronic topological transition; In detail, through first-principle calculations, a phase transition from a semiconductor to topological insulator occurs at a low-pressure range.…”
Section: Phonon Dynamicsmentioning
confidence: 91%